2017
DOI: 10.1021/acsnano.7b01894
|View full text |Cite
|
Sign up to set email alerts
|

Fully Stretchable Optoelectronic Sensors Based on Colloidal Quantum Dots for Sensing Photoplethysmographic Signals

Abstract: Flexible and stretchable optoelectronic devices can be potentially applied in displays, biosensors, biomedicine, robotics, and energy generation. The use of nanomaterials with superior optical properties such as quantum dots (QDs) is important in the realization of wearable displays and biomedical devices, but specific structural design as well as selection of materials should preferentially accompany this technology to realize stretchable forms of these devices. Here, we report stretchable optoelectronic sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 36 publications
(51 reference statements)
0
96
0
1
Order By: Relevance
“…The buckling mechanism (e.g. wrinkled or wavy structure) 9,15,37,45 has been proven to be an effective strategy for fabricating stretchable devices from non-stretchable materials 36 , as the applied stress can be effectively absorbed by expansion of the buckled structure until fully straightened, and also the adhesion of the ink is improved 46 . Thus, the stretchability performance was dependent on the level of pre-strain 47 and electrically active areas of Ag-DS/CF were observed to remain intact during repeatable stretching up to strains of 75% in the direction of the X-axis for configuration 50.…”
Section: Resultsmentioning
confidence: 99%
“…The buckling mechanism (e.g. wrinkled or wavy structure) 9,15,37,45 has been proven to be an effective strategy for fabricating stretchable devices from non-stretchable materials 36 , as the applied stress can be effectively absorbed by expansion of the buckled structure until fully straightened, and also the adhesion of the ink is improved 46 . Thus, the stretchability performance was dependent on the level of pre-strain 47 and electrically active areas of Ag-DS/CF were observed to remain intact during repeatable stretching up to strains of 75% in the direction of the X-axis for configuration 50.…”
Section: Resultsmentioning
confidence: 99%
“…157 In 2017, Kim et al reported wearable photoplethysmographic (PPG) sensors that combined stretchable QLEDs and QD photodetectors. 158 The graphene-based transparent electrode provided extreme bendability for the QD-based LEDs and PDs. The QLED was transferred onto a prestrained elastomer to form a buckled structure, and displayed 70% stretchability.…”
Section: Flexible Qleds Integrated With Other Electronic Devicesmentioning
confidence: 99%
“…In addition to the QD layers, transfer printing methods can apply to multilayer stacks that include the QD emitting layers, charge transport layers, conductive electrodes, and even substrate layers. [49c,53] By using a sacrificial fluoropolymer to provide low energy surfaces for release, this type of multilayer transfer printing process allows the incorporation of red‐ and green‐emitting QD assemblies with different, optimized electron transport layers (ZnO and TiO 2 ) and the same hole transport/anode layers. [49c] The independently tailored band alignments between green QDs/TiO 2 and red QDs/ZnO and well‐matched highest occupied molecular orbitals (HOMO)/lowest unoccupied molecular orbitals (LUMO) levels result in improved charge carrier injection efficiencies and accordingly higher EQEs.…”
Section: Flexible Quantum Dot Leds (Qleds)mentioning
confidence: 99%
“…[49c] The independently tailored band alignments between green QDs/TiO 2 and red QDs/ZnO and well‐matched highest occupied molecular orbitals (HOMO)/lowest unoccupied molecular orbitals (LUMO) levels result in improved charge carrier injection efficiencies and accordingly higher EQEs. Furthermore, the capability for transfer printing the entire QLED stack to prestrained elastomeric substrates yields fully stretchable, wavy QLED arrays through buckling processes . The bending radii in such systems can be as small as 35 µm without mechanical damage or electrical degradation.…”
Section: Flexible Quantum Dot Leds (Qleds)mentioning
confidence: 99%
See 1 more Smart Citation